Prevalence of Underweight, Stunting, and Wasting among Children Infected with Human Immunodeficiency Virus in South India - C. Padmapriyadarsini; N. Pooranagangadevi; K. Chandrasekaran; Sudha Subramanyan; C. Thiruvalluvan; P. K. Bhavani; Soumya Swaminathan (Hindawi Limited, 2009)
Background. Growth failure is a common feature of children with human immunodeficiency virus (HIV) infection. Malnutrition increases mortality and may impair the response to antiretroviral treatment. Objective. Our objective was to describe the prevalence of stunting, underweight, and wasting in HIV-infected children in south India and to assess the utility of these parameters in predicting immune status. Methodology. In this cross-sectional study, anthropometric measurements and CD4 counts were performed on 231 HIV-infected children. 𝑍 scores for height for age, weight for age, and weight for height were correlated with CD4 cell counts and receiver operating characteristic curves plotted. Results. Prevalence of underweight was 63%, stunting 58%, and wasting 16%, respectively. 33-45% of children were moderately or severely malnourished even at CD4 >25%; sensitivity and specificity of stunting or underweight to predict HIV disease severity was low. Conclusions. Undernutrition and stunting are common among HIV-infected children at all stages of the disease in India. Early and aggressive nutritional intervention is required, if long-term outcomes are to be improved.